A new checklist of lichenized fungi occurring in Thailand - Kawinnat Buaruang; Kansri Boonpragob; Pachara Mongkolsuk; Ek Sangvichien; Kajohnsak Vongshewarat; Wetchasart Polyiam; Achariya Rangsiruji; Wanaruk Saipunkaew; Khwanruan Naksuwankul; Jutarat Kalb; Sittiporn Parnmen; Ekaphan Kraichak; et al. (My University, 2017)
A new revised checklist of lichenized fungi in Thailand is presented, including 1,292 species. Recent work on the taxonomy of these organisms in Thailand resulted in an enormous increase in our knowledge of the lichen biota of the country – the current checklist includes more than twice as many species as the previous catalogue published 15 years ago – and phylogenetic studies resulted in numerous changes in the generic classification of lichenized fungi. Hence, a new checklist is here presented summarizing the current knowledge of lichens in Thailand. Six new records are reported, viz. Acanthothecis salazinica, Bactrospora metabola, Buellia parastata, Diploschistes cinereocaesius, Rolfidium coccocarpioides, and Trapelia placodioides. Five previously recorded species, namely Lecanora carpinea, Platismatia glauca, P. lacunosa, P. tuckermanii and Roccella phycopsis are shown to be based on misidentifications and are excluded from the checklist. Three new combinations of species previously placed in Pertusaria to Lepra are proposed: L. bulolensis (A.W.Archer, Elix & Streimann) Schmitt & Lumbsch, L. patellifera (A.W.Archer) Schmitt & Lumbsch, and L. subventosa (Malme) Schmitt & Lumbsch. Asia, biodiversity, lichens, new records, taxonomy
Keywords: Biota; Global biodiversity; Lichen and fungal ecology